Data Interpretation

• ( 2 ) (a/b)x - 1 = (b/a)x - 3, then the value ofx is:

• 1) 1/2
• 2) 1
• 3) 2
• 4) 3 1/2
• Discussion in forum
Solution : (a/b)x - 1 = (b/a)x - 3
=> (a/b)x - 1 = (a/b)3 - x
=> x - 1 = 3 - x
=> 2x = 4
=> x=2

discussion

• ( 3 ) Simplify : (8/125)- 4/3

• 1) 625/16
• 2) 512/16
• 3) 256/8
• 4) 625/8
• Discussion in forum
Solution : (8/125)- 4/3
=> (125/8) 4/3
=> (5/2)3*(4/3)
=> (5/2) 4 = 625/16

discussion

• ( 4 ) If 2x + 3z = 17 and 2x + z - 3z + 1 = 5, the value of x and z respectively are:

• 1) 2,and 3
• 2) 3 and 2
• 3) 4 and 3
• 4) 3 and 4
• Discussion in forum
Answer : 2) 3 and 2
Solution : Given, 2x + 3z = 17 and 2x + z - 3z + 1 = 5
=> 22 2x - 3*3z = 5
or A + B = 17 and 4A - 3B = 5, where A = 2x and B = 3z.
On solving, we get : A = 8 and B = 9.
A = 2x = 8 = 23
B = 3z = 9 = 32.
x = 3 and z = 2

discussion

Answer : 2) 3 and 2

• ( 5 ) Simpify : (1024)-4/5

• 1) 256
• 2) 1/256
• 3) 512
• 4) 1/512
• Discussion in forum
Solution : (1024)-4/5) = (1/1024)4/5 = (1/2)10*4/5 = (1/28) = 1/256.

discussion

• ( 6 ) if ax = by = cz and b2 = ac then y equal to:

• 1) xz/(x+z)
• 2) xz/2(x-z)
• 3) xz/2(z-x)
• 4) 2xz/(x+z)
• Discussion in forum
Solution : Let ax = by = cz = k.
Then, a = k1/x, b = k1/y, c = k1/z
given, b2 = ac
=> k2/y = k1/x . k1/z => k(1/x) + (1/z)
2/y = (1/x) + (1/z) or 2/y = (x + z)/xz or y = 2xz/(x + z).

discussion

• ( 7 ) Simplify : (256/576)1/4 * (64/27)-1/3 * (216/8)-1

• 1) 1/(3√ 16)
• 2) 1/(18√ 6)
• 3) 1/(2√ 6)
• 4) 1/(3√ 7)
• Discussion in forum
Solution : (256/576)1/4 * (64/27)-1/3 * (216/8)-1
=> (256/576)1/4 * (27/64)1/3 * (8/216)1
=> (44/242)1/4 * (3/4)3*1/3 * (8/216)
=> (4/√ 24) * (3*8)/(4*216)
=> (4/2√ 6) * (1/36)
=> 1/18√ 6.

discussion

• ( 8 ) (1/4ab2c)2 ÷ (3/2a2bc2)4

• 1) (ac)2/81
• 2) (ac)6/81
• 3) (ac)4/81
• 4) (ac)7/81
• Discussion in forum
Solution : (1/4ab2c)2 ÷ (3/2a2bc2)4
=> (1/16a2b4c2)*(24a8b4c8)/34
=> (1/16b2)*(16a6c6)/81
=> (ac)6/81

discussion

• ( 9 ) If √(2n) = 64, then the value of n is:

• 1) 2
• 2) 4
• 3) 6
• 4) 12
• Discussion in forum
Solution : √(2n) = 64
=> (2n) = 642
=> (2n) = (26)2
=> 2n = 212
=> n = 12.

discussion

• ( 10 ) simplify : (5x * 25x - 1) ÷ (5x- 1 * 25x - 1)

• 1) 2
• 2) 7
• 3) 5
• 4) 9
• Discussion in forum
Solution : (5x * 25x - 1) ÷ (5x - 1 * 25x - 1)
=> (5x * (52)x - 1) ÷ (5x - 1 * (52)x - 1)
=> (5x * 52x - 2) ÷ (5x - 1 * 52x - 2)
=> (53x - 2) ÷ (53x - 3)
=> 53 - 2 = 5.

discussion